Kemampuan Komunikasi Matematis Siswa SMP Kelas VIII di Kampung Cigulawing - Ismayanti, Sri; Sofyan, Deddy (Department of Mathematics Education Program IPI Garut, 2021)
Penelitian ini dilatarbelakangi oleh kemampuan komunikasi matematis siswa yang masih rendah. Tujuan penelitian untuk memperoleh deskripsi kemampuan komunikasi matematis siswa kelas VIII pada pembelajaran matematika. Metode penelitiannya deskriptif kualitatif. Subjek penelitian adalah 4 siswa kelas VIII SMP Negeri 7 Garut. Hasil penelitian menunjukkan (1) Kemampuan komunikasi matematis siswa pada materi Penyajian Data kelas VIII SMP Negeri 7 Garut di Kampung Cigulawing, secara umum dikatakan kurang baik. Dikarenakan sebagian besar siswa belum mampu memenuhi semua indikator; (2) Siswa dengan kemampuan matematika tinggi mampu mencapai hampir seluruh indikator kemampuan komunikasi matematika; (3) Siswa dengan kemampuan matematika sedang kurang menguasai beberapa indikator kemampuan komunikasi matematis; (4) Siswa dengan kemampuan matematika rendah belum mampu menguasai indikator kemampuan komunikasi matematis. This research is motivated by the students' low mathematical communication skills. The research objective was to obtain a description of the students' mathematical communication skills in class VIII in mathematics learning. The research method is descriptive qualitative. The research subjects were 4 grade VIII students of SMP Negeri 7 Garut. The results showed (1) the students' mathematical communication skills in the data presentation material of class VIII SMP Negeri 7 Garut in Cigulawing Village, were generally said to be less good. Because most students have not been able to meet all the indicators; (2) Students with high mathematical abilities can achieve almost all indicators of mathematical communication skills; (3) Students with moderate mathematical abilities have not mastered several indicators of mathematical communication skills; (4) Students with low math abilities have not been able to master the indicators of mathematical communication skills.